Hybrid Drugs for Malaria - Walsh, J. J.; Bell, A. (Current Pharmaceutical Design, 2009)
Malaria continues to devastate much of the tropics and sub-tropics in spite of the availability of a number of antimalarial drugs. Part of this problem is due to the disadvantages of the drugs in use, which include (depending on the drug) side effects, reduced efficacy due to resistance, and high cost. Multiple traditional and novel approaches to the discovery and design of new antimalarial agents are likely to be required to furnish the new drugs necessary for improved malaria control. This review will address one novel and emerging approach, namely the development of hybrid antimalarial agents composed of two distinct antimalarial moieties joined covalently. Particular emphasis will be placed on the properties of the hybrids' design, including biological activity, advantages over other approaches, and the potential to address issues relating to resistance, solubility and formulation/delivery. The review will discuss the synthetic methodology used to form the hybrid and the ease by which it may be cleaved to form the independent components in vivo. The molecules discussed include hybrids of (i) artemisinins or other endoperoxide-based agents and quinolines (e.g. trioxaquines), (ii) chloroquine or other aminoquinolines and resistance-reversing or other agents, and (iii) peptidase inhibitors and other agents. The actual and potential advantages and disadvantages of such hybrids in relation to established single drugs or drug combinations will be discussed critically and promising future directions highlighted.
Keywords: chloroquine